Chronic pelvic pain: a comprehensive review on its physical and mental effects - Mohapatra, Ipsita; Samantaray, Subha Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Chronic pelvic pain (CPP) is a multifaceted and often debilitating condition that affects a significant portion of the female population wherein there is persistent acyclic pain in the pelvic region continuing for a long period of time. It has multifactorial etiology which may encompass gynecological, urological, gastrointestinal, musculoskeletal, and neurological components. This comprehensive review highlights the physical and psychological effects of CPP and briefly summarizes the various treatment modalities for CPP.